تداعيات جائحة كورونا على قطاع النقل الجوي الدولي وقطاع النقل الجوي في الجزائر - دالع، سعيد (جامعة زيان عاشور بالجلفة, 2022)
لقد أدت جائحة كورونا منذ الإعلان عنها من طرف منظمة الصحة الدولية في مارس 2020 إلى تعليق الرحلات الجوية الدولية والداخلية بصفة جزئية في بعض الدول، وبصفة كلية في دول أخرى. هذا الشلل الذي أصاب قطاع النقل الجوي كان السبب في خسائر اقتصادية فادحة تكبدها مشغلوا قطاع الطيران المدني، وذلك حسب ما ورد في تقارير الهيئات الدولية. أمام هذا الوضع سارعت دول العالم المنضوية تحت مظلة هاته الهيئات ومن بينها الجزائر إلى وضع خطط جاءت في شكل توصيات ونصوص قانونية هدفها الأول تقديم الدعم بمختلف أشكاله لقطاع الطيران المدني من أجل التخفيف من حدة الآثار الاقتصادية والاجتماعية التي خلفتها جائحة كورونا، وإعادة إنعاش الحركة الجوية على المستوى الدولي والداخلي، وكهدف ثان وضع استراتيجية مستقبلية لضمان التعافي الكلي لهذا القطاع وعودته إلى تحقيق النمو الاقتصادي المعهود مع الأخذ بعين الاعتبار تطور الحالة الوبائية في العالم. The Corona pandemic, since it was announced by the World Health Organization in March 2020, has resulted in the partial suspension of international and local flights in some countries, and completely in other countries. This paralysis that has afflicted the air transport sector has been the cause of heavy economic damages suffered by operators in the civil aviation sector, according to reports by international organizations. Faced with this situation, the countries of the world under its supervision, including Algeria, hastened to draw up plans which have materialized in recommendations and law, whose primary objective is to provide various forms of support to the civil aviation sector, in order to mitigate the economic and social effects left by the Corona pandemic and to revitalize international and national air traffic. The second objective was to develop a future strategy to ensure the overall recovery of this sector and its return to the usual economic growth, taking into account the evolution of the epidemiological situation in the world.
Keywords: الإجراءات الاحترازية -- الخطوط الجوية -- الجزائر